Cultural Lexicon in the Siraman Ceremony of the Javanese Community in Muara Jaya Village, Rokan Hulu: An Ethnolinguistic Study - Rohana, Dewi; Aihua, Yan; Hernandez, Hjalmar Punla; Esquivel, Mary Ann; Wattanaboot, Ladawan (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to inventory, classify, and analyze the cultural lexicon found in the Javanese Siraman wedding ritual performed by the diaspora community in Muara Jaya Village, Rokan Hulu Regency, as well as to describe its semantic and symbolic meanings. Methodology: This research employs a descriptive qualitative method with an ethnolinguistic approach. Data were collected through participant observation, in-depth interviews with five purposively sampled key informants (customary leaders, ceremony guides, and bridal makeup artists), and audio-visual documentation of the ritual speech and procedures. Main Findings: The research identified 67 cultural lexicons in the Siraman ritual, classified into eight semantic categories: (1) ritual equipment (12 lexicons), (2) flowers and plants (15 lexicons), (3) water and purification (5 lexicons), (4) actions and procedures (18 lexicons), (5) actors/officiants (8 lexicons), (6) spatial concepts (3 lexicons), (7) time concepts (4 lexicons), and (8) currency/transaction (2 lexicons). Semantic analysis reveals that these lexicons contain philosophical meanings related to fertility, purity, prosperity, harmony, and cosmology. Lexical erosion was found among the younger generation, marked by 60% unfamiliarity with key terms such as dulangan pungkasan, kreweng, and gendhongan. Novelty/Originality of this study: This study is the first to systematically document the ethnolinguistic aspects of the Siraman tradition in a Javanese transmigration community in Sumatra. It contributes to the preservation of endangered Javanese cultural lexicon and offers a model for lexical documentation in diaspora communities.